(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Co-infection of HIV and TB is a significant public health concern, as these two diseases can interact and worsen each other’s effects, leading to more severe health outcomes. The objective of this study was to stratify CD4 count according to different presentations of TB and see their association in HIV/TB co-infected patients. Other objective was to establish the predictive value of CD4 count for different sites of involvement. Patients and methods: This cross-sectional observational study was conducted from October 2022 till March 2023. A total of seventy-four outdoor and indoor patients were enrolled. Patients aged more than 18 years having confirmed HIV and TB infections were included in the study. Those having any other opportunistic infection and aged less than 18 any having only presumed TB infection were excluded from the study. Patient’s data was collected using a predesigned and pretested questionnaire after taking consent and ensuring confidentiality. Baseline CD4 count were recorded and stratified into <100 and >100 CD4 counts. Results: Mean age of the patients was 38.33 (range = 21-78 years), out of which 67 (90.5%) were male and 7 (9.5%) were female. Most frequent was pulmonary TB 34 (46.0%) followed by disseminated TB 13 (17.5%), TB meningitis 10 (13.5%), and pleural TB 08 (10.8%) and others 09 (12.2%). There was no association found between CD4+ T-lymphocyte count and site of involvement of TB. Spearman co-efficient showed no relationship between CD4 count and site of involvement. Conclusion: The Stratification of CD4 count does not show any specific trend for TB site involvement in TB/HIV co-infected patients. No association was found between CD4+ Lymphocyte count and site of involvement of TB in this study. Cut-off predictive value came out to be 53.3 in our study using receiver operating curve.